Endophytic Bacteria Identification of Red Ginger (Zingiber officinale var. Rubrum) From Enggano Island - Welly Darwis; Annisa Prastika Supriyanto; Risky Hadi Wibowo; Sipriyadi Sipriyadi; Rochmah Supriati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: Endophytic bacteria are bacteria associated with the tissues of healthy plants that are beneficial. Almost every higher plant has some endophytic bacteria, one of which is Red Ginger (Zingiber officinale var. Rubrum) from Enggano Island. This research aims to obtain endophytic bacteria and to identify the Red Ginger (Zingiber officinale var. Rubrum) endophytic bacteria collected from Enggano Island. Endophyte bacteria isolation was carried out by the paste method on medium Nutrient Agar (NA) after sterilizing the surface of plant organs using alcohol and sodium hypochlorite 5,25%. A total of 24 isolates of endophytic bacteria of Red Ginger (Zingiber officinale var. Rubrum) were isolated from rhizomes (stem modification), leaf sheath, and leaf sheet. Endophytic bacteria were identified based on morphological observation, biochemical tests, and Gram-staining. As a result, the diversity of bacteria consists of 7 genera, namely the genus Bacillus, Sporosarcina, Amphibacillus, Azotobacter, Eubacterium, Pimelobacter, and Micrococcus. The genus Bacillus consists of 4 species, the genus Sporosarcina consists of 6 species, the genus Amphibacillus consists of 1 species, the genus Azotobacter consists of 2 species, the genus Eubacterium consists of 1 species, the genus Pimelobacter consists of 1 species, and the genus Micrococcus which also consists of 1 species. Bacillus is the most common type of endophytic bacteria that was found in red ginger from Enggano Island.Abstrak: Bakteri endofit adalah bakteri yang berasosiasi dengan jaringan tanaman yang memiliki banyak manfaat, baik bagi manusia maupun tumbuhan itu sendiri. Hampir setiap tumbuhan tingkat tinggi memiliki beberapa bakteri endofit, salah satunya jahe merah (Zingiber officinale var. Rubrum) yang berasal dari Pulau Enggano. Penelitian ini bertujuan untuk mendapatkan bakteri endofit dan mengetahui keanekaragaman bakteri endofit yang diisolasi dari jahe merah (Zingiber officinale var. Rubrum) asal Pulau Enggano. Isolasi bakteri endofit dilakukan dengan metode tempel pada media Nutrient Agar (NA) setelah dilakukan sterilisasi permukaan organ tanaman menggunakan alkohol dan natrium hipoklorit 5,25%. Sebanyak 24 isolat bakteri endofit jahe merah (Zingiber officinale var. Rubrum) diisolasi dari rimpang (modifikasi batang), pelepah daun, dan helaian daun. Bakteri endofit diidentifikasi berdasarkan pengamatan morfologi, uji biokimia, dan pewarnaan Gram. Hasilnya, keanekaragaman bakteri terdiri dari 7 genus, yaitu Bacillus, Sporosarcina, Amphibacillus, Azotobacter, Eubacterium, Pimelobacter, dan Micrococcus. Genus Bacillus terdiri dari 4 spesies, genus Sporosarcina terdiri dari 6 spesies, genus Amphibacillus terdiri dari 1 spesies, genus Azotobacter terdiri dari 2 spesies, genus Eubacterium terdiri dari 1 spesies, genus Pimelobacter terdiri dari 1 spesies, dan genus Micrococcus yang juga terdiri dari 1 spesies. Bacillus merupakan genus yang mendominasi keanekaragaman bakteri endofit yang diisolasi dari jahe merah asal Pulau Enggano.